Penerapan Metode Rapid Application Development pada Sistem Informasi Persediaan Barang berbasis Web - Biktra Rudianto; Yuni Eka Achyani (Bianglala Informatika, 2020)
At this time information technology is developing very rapidly and requires business actors to be able to follow the developments and advances of the times, especially in the world of technology and information. Inventory of merchandise is a company asset that is one of the assets included in current assets. Merchandise inventories are company assets that are purchased and stored to be resold and make a profit. Recording of merchandise inventory that is still manual, such as data collection of incoming goods, demand for goods, delivery of goods, returns of goods to the preparation of reports will certainly result in the accumulation of goods request notes. The difficulty of data collection of requests for goods from branches to deliver goods, errors in goods requested and sent, the length of time to record the return of goods, errors in calculating the stock of goods and difficulty in obtaining reports when needed are also one of the obstacles in the process of merchandise inventory. Therefore, a web-based inventory information system is needed in order to make it easier for users to manage the inventory process of their merchandise, so that it can simplify the process of recording, storing, searching and making reports. In designing a web-based inventory information system, the author uses the Rapid Application Development (RAD) method. This information system is the best solution for solving problems in managing inventory. With the use of computer data technology, managed data becomes faster, reduces time inefficiency and reduces the occurrence of errors in processing data.